1997
DOI: 10.1038/sj.ijo.0800413
|View full text |Cite
|
Sign up to set email alerts
|

Influence of obesity on plasma lipoproteins, glycaemia and insulinaemia in patients with familial combined hyperlipidaemia

Abstract: The in¯uence of obesity on blood pressure and plasma lipoproteins, glucose and insulin levels was investigated in patients with familial combined hyperlipidaemia (FCH). Sixty seven FCH patients mean age 49.0 AE 8.9 y (45 male, 22 female) de®ned as obese (BMI ! 27 kg/m 2 , n 39) or non-obese (BMI`27 kg/m 2 , n 28) were compared with control subjects matched for age, gender and body weight. Blood pressure, plasma lipoproteins, glucose and insulin were measured at baseline and following standard oral glucose load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Subjects with FCHL present with a complex phenotype whose expression is influenced by genetic, metabolic, and environmental factors. [3][4][5][6] Affected FCHL relatives are viscerally obese, 2,4,7 hyperinsulinemic, 3 insulin-resistant, 5,7 and can show a number of abnormalities in lipid metabolism: hypercholesterolemia and/or hypertriglyceridemia, elevated apolipoprotein B (apoB) levels, small dense low-density lipoprotein (sd LDL), and decreased plasma high-density lipoprotein (HDL) cholesterol concentrations.…”
mentioning
confidence: 99%
“…Subjects with FCHL present with a complex phenotype whose expression is influenced by genetic, metabolic, and environmental factors. [3][4][5][6] Affected FCHL relatives are viscerally obese, 2,4,7 hyperinsulinemic, 3 insulin-resistant, 5,7 and can show a number of abnormalities in lipid metabolism: hypercholesterolemia and/or hypertriglyceridemia, elevated apolipoprotein B (apoB) levels, small dense low-density lipoprotein (sd LDL), and decreased plasma high-density lipoprotein (HDL) cholesterol concentrations.…”
mentioning
confidence: 99%
“…[11][12][13] This observation indicates that overweight is only a modifying factor for insulin sensitivity in FCHL. 14 A defect in insulin action in adipose tissue is likely to play a significant role in FCHL because insulin's suppressive effect on free fatty acid (FFA) levels is impaired in FCHL patients. 10,12,15 High FFA levels may in turn lead to both a decrease in insulin-stimulated glucose uptake in adipose tissue and skeletal muscle, according to the scheme proposed by Randle et al, 16 and to an increase in the synthesis of lipoproteins in the liver.…”
mentioning
confidence: 99%
“…Because patients with FCHL have several components of the metabolic syndrome, e.g., hypertriglyceridemia (2,3), postprandial lipemia (33), high prevalence of small, dense LDL particles (14,34,35), low HDL cholesterol levels (36,37), and central obesity (38), it is not surprising that these patients also have hyperinsulinemia (33,37) as a result of insulin resistance (4 -6). Our earlier studies suggested that insulin resistance also is present in young relatives of FCHL patients who are at risk to develop FCHL.…”
Section: Discussionmentioning
confidence: 99%